2006
DOI: 10.1111/j.1365-2036.2006.02934.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in chronic liver patients

Abstract: SUMMARY Background and aimHealth-related quality of life of patients with chronic liver disease has been shown to be impaired in numerous studies. However, the factors which influence health-related quality of life in treated chronic liver patients are not quite known. This is the first study to assess the impact of physical and psychosocial determinants on a weighted score of health-related quality of life in patients with chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
109
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 32 publications
10
109
2
4
Order By: Relevance
“…The majority of studies have analyzed viral etiology of CLD followed by alcoholic liver disease, NASH, holestatic liver disease, autoimmune hepatitis, and medicamentous hepatitis [13][14][15]. There are concordant results in other similar studies regarding the average age of participants, gender, marital status, and educational status [8,[15][16][17].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The majority of studies have analyzed viral etiology of CLD followed by alcoholic liver disease, NASH, holestatic liver disease, autoimmune hepatitis, and medicamentous hepatitis [13][14][15]. There are concordant results in other similar studies regarding the average age of participants, gender, marital status, and educational status [8,[15][16][17].…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, an increasing number of patients with "mild" distress was a characteristic for the group of patients with cirrhosis, but without statistical significance in terms of frequency distribution. Our results differ from literature data [14]. According to the most relevant studies, generic QoL score (mainly assessed by SF-36 questionnaire) was significantly lower within the patients with CLD compared with healthy controls, including the studies of Bondini et al [20], which indicate significantly lower SF-36 scores in patients with cholestatic liver diseases and viral hepatitis C in comparison with the control group.…”
Section: Discussioncontrasting
confidence: 57%
“…The SF-36 has been compared to the CLDQ in a number of studies. Reasonably good correlations between the SF-36/SF-6D and CLDQ for most domains were found and similar changes in both tools with disease progression have been reported (28)(29)(30). We, therefore, feel the SF-36 is a suitable tool for calculating costeffectiveness of the two procedures.…”
Section: Discussionmentioning
confidence: 85%
“…34,37 Gutteling et al 37 applied linear regression analyses to the results of the Liver Disease Symptom Index 2.0 and the Short Form 6D to assess the impact of quality-of-life determinants on patients with chronic liver disease and found that fatigue was strongly related to HRQL (B ϭ Ϫ0.030). However, the relationship between fatigue and liver disease is not yet determined.…”
mentioning
confidence: 99%